The Role of New Instruments in the Musical Works of Composers/Sound Artists in Indonesia. - Cahyo, Septian Dwi (Contemporary Music Review, 2024)
Since the 1980s, Indonesian sound artists/composers have been creating new instruments as part of their compositional work. Some of them invented new instruments to expand the tradition, while others used their new instruments to address current political issues in their communities. This phenomenon prompted me to investigate and analyse their works, which led to two conclusions. First, some sound artists/composers create new musical instruments to expand traditions, introduce new contexts and create their desired sound worlds. Second, the new musical instruments they create also act as visual art, serving as symbolic representations of society's problems.